2010
DOI: 10.1038/hr.2010.27
|View full text |Cite
|
Sign up to set email alerts
|

The influence of posture on the estimation of daily salt intake by the second morning urine method

Abstract: The second morning urine (SMU) method was developed to evaluate daily salt intake, but the posture that should be adopted until the SMU collection remains unclear. This study investigated the influence of posture in hypertensive patients who underwent this test. The subjects were 100 patients who could collect 24-h urine samples correctly and were on a diet containing 7 g of salt per day. Their daily salt intake was estimated for three consecutive days in the recumbent, sitting, and sitting and standing positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Second, the influence of posture on the estimate was not evaluated. When using Kawasaki's equation, it is suggested that the urine should be collected in a sitting or standing position to maintain accuracy [19]. All of the patients who participated in this study were outpatients, and they probably collected the first morning urine just after they woke up.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the influence of posture on the estimate was not evaluated. When using Kawasaki's equation, it is suggested that the urine should be collected in a sitting or standing position to maintain accuracy [19]. All of the patients who participated in this study were outpatients, and they probably collected the first morning urine just after they woke up.…”
Section: Discussionmentioning
confidence: 99%
“…12 Daily salt intake is evaluated by measuring the ratio of sodium to creatinine in the SMU specimen and by calculating daily creatinine excretion as reported previously. 13 We have found that the accuracy of estimating the daily salt intake by the SMU method is equal to that of the 24UC method if the subject maintains the sitting or standing position until the SMU sample is collected, 14 and we have also shown that this method was useful in patient on antihypertensive therapy. 14,15 On the other hand, Tanaka et al 16 have developed a simple casual urine (CU) method for public health research.…”
Section: Introductionmentioning
confidence: 82%
“…13 We have found that the accuracy of estimating the daily salt intake by the SMU method is equal to that of the 24UC method if the subject maintains the sitting or standing position until the SMU sample is collected, 14 and we have also shown that this method was useful in patient on antihypertensive therapy. 14,15 On the other hand, Tanaka et al 16 have developed a simple casual urine (CU) method for public health research. With the CU method, a urine sample can be collected during the daytime between 0800 hours and 1900 hours, whereas urine is generally collected between 0800 hours and 1000 hours for the SMU method.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Urinary concentrations of sodium (Na), potassium (K) and creatinine (Cr) were measured, and 24-h excretions of Na and K were estimated by our established method. [23][24][25][26][27] To confirm the consistency of the participants' diet over the study period, urinary concentrations of calcium (UCa) and magnesium (UMg) were also measured, and the UCa/UMg ratio was calculated. Urinary urea nitrogen (UN) was measured and the UN/UCr the ratio was calculated before and after the study period for each participant to roughly estimate the stability of the nutrient intake.…”
Section: Urinary Excretion Of Electrolytesmentioning
confidence: 99%